Investigations in sociohistorical linguistics : stories of colonisation and contact - Trudgill, Peter (New York : Cambridge University Press, 2010)
"In the last five hundred years or so, the English language has undergone remarkable geographical expansion, bringing it into contact with other languages in new locations. It also caused different regional dialects of the language to come into contact with each other in colonial situations. This book is made up of a number of fascinating tales of historical-sociolinguistic detection. These are stories of origins - of a particular variety of English or linguistic feature - which together tell a compelling general story. In each case, Trudgill presents an intriguing puzzle, locates and examines the evidence, detects clues that unravel the mystery, and finally proposes a solution. The solutions are all original, often surprising, sometimes highly controversial. Providing a unique insight into how language contact shapes varieties of English, this entertaining yet rigorous account will be welcomed by students and researchers in linguistics, sociolinguistics and historical linguistics"--
Sadržaj: Machine generated contents note: Prologue: colonisation and contact; 1. What really happened to Old English?; 2. East Anglian English and the Spanish Inquisition; 3. On Anguilla and The Pickwick Papers; 4. The last Yankee in the Pacific; 5. An American lack of dynamism; 6. Colonial lag?; 7. 'The new non-rhotic style'; 8. What became of all the Scots?; Epilogue: the critical threshold and interactional synchrony
Bibliografija: str. 193-211.
Bilješke uz tekst.
Imensko kazalo
Keywords: sociolingvistika; povijesna lingvistika; jezici u kontaktu; kolonizacija : jezici